2011
DOI: 10.1021/jf104831n
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline N-Oxide: Its Mutagenicity and Possible Role as Ultimate Carcinogen in Areca Oral Carcinogenesis

Abstract: The areca nut is the most widely consumed psychoactive substance in Taiwan, India, and Southeast Asia. It is considered to be an environmental risk factor for the development of oral submucous fibrosis and cancer. Arecoline, the major alkaloid of areca nut, has been known to cause cytotoxicity and genotoxicity in various systems. However, the active compound accounting for arecoline-induced damage in normal human oral cells is still uncharacterized. The present study was undertaken to identify the active metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…4 Previous studies identified that arecoline, arecaidine, guvacoline, and guvacine are the four major alkaloids among the chemical constituents of the areca nut. 5 Arecoline, the most abundant and active alkaloid, is suggested to be a potential carcinogen. 4 Besides its reported cytotoxic effects on cultured oral cells, studies with bacteria, mammalian cells, and experimental animals have revealed arecoline's mutagenic and genotoxic effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4 Previous studies identified that arecoline, arecaidine, guvacoline, and guvacine are the four major alkaloids among the chemical constituents of the areca nut. 5 Arecoline, the most abundant and active alkaloid, is suggested to be a potential carcinogen. 4 Besides its reported cytotoxic effects on cultured oral cells, studies with bacteria, mammalian cells, and experimental animals have revealed arecoline's mutagenic and genotoxic effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was reported to be mutagenic in Salmonella (TA100, TA1535, TA98 and TA1538), and the mutagenicity was enhanced in the presence of S9 (TA98 and TA 100) [14,15]. Another report suggested that arecoline was weakly mutagenic in TA98 and TA100 only under metabolic activation [16]. In mammalian cell mutagenicity assays, arecoline induced 8-azaguanine resistant mutation in Chinese hamster V79 cells [17] and increased chromosomal aberrations, sister-chromatid exchanges in Chinese hamster ovary (CHO) cells [18] and elicited ␄-H2AX phosphorylation and suppresses DNA repair [12].…”
Section: Introductionmentioning
confidence: 99%
“…The broad bands centered at 3450 cm −1 and 1587 cm −1 in the spectrum of BiOI corresponded to the stretching and bending vibrations of O-H, respectively. Moreover, the band at 489 cm −1 for both samples of pure BiOI and CdS/BiOI nanocomposites was associated with the stretching vibrations of the Bi-O [30]. In comparison with the spectrum of BiOI, the weak absorption band at 618 cm −1 could be ascribed to the Cd-S group which was in the spectrum of the CdS/BiOI nanocomposites.…”
Section: Ft-ir Analysismentioning
confidence: 88%